Adjustable temperature array for characterizing ecological and evolutionary effects on thermal physiology. Issue 8 (3rd July 2019) - Cocciardi, Jennifer M.; Hoskin, Conrad J.; Morris, Wayne; Warburton, Russell; Edwards, Lexie; Higgie, Megan
Abstract: To accurately characterize a species' thermal niche and aid in predicting effects of climate change we must not only include information on thermal tolerances and physiological responses to changing temperatures, but also incorporate ecological effects and evolutionary processes that may shape a species' niche. However, quickly and practically collecting data on key factors such as adaptation potential, behaviour, effects of species interactions, plasticity and thermal tolerances is logistically challenging. We have therefore created an adjustable temperature array (ATA) to assist with experimental ecology and evolution research. ATA's are a row of independent temperature points controlled and set by the user and made from commercially available parts. This allows the user to create unique thermal landscapes relevant to their study organism(s) and question(s). Further, the option of using an enclosed cage allows the user to answer questions at the individual, population, or community level in the context of changing thermal environments. ATA's are able to be user‐set to constant or dynamic temperature regimes and are designed for use on small animals (e.g. fruit flies, beetles, mosquitoes) or plants (e.g. germinating seeds). We have tested and confirmed the accuracy of the ATA to several thermal landscapes that would be useful for experimental ecology and evolution, including: (a) coarse resolution of a broad thermal niche ranging from 12° to 42°C in 2°C intervals ( R 2  = 0.998); (b) fine resolution of a narrow thermal niche ranging from 15° to 32°C in 1°C intervals ( R 2  = 0.997); (c) a pyramid‐shaped niche consisting of a gradient from 14° to 30°C in 2°C intervals ( R 2  = 0.997); and (d) a very narrow thermal niche with replicate thermal resources ranging from 26.5° to 34°C in 1.5°C intervals ( R 2  = 0.989). The equipment described here is an important tool for thermal niche studies and will aid in gathering information on effects of ecological and evolutionary processes to create a comprehensive picture of species responses to climate change.